Optimalisasi Literasi Digital Dalam Meningkatkan Kualitas Pembelajaran Di Sekolah Dasar: Model Pendampingan Berbasis Komunitas Belajar Guru - Reza Rachmadtullah; Imas Srinana Wardani; Rarasaning Sariyaningsih (Pusmedia Group Indonesia, 2026)
The low utilization of digital technology in elementary school learning largely stems from a weak culture of knowledge sharing among teachers, not solely from limited resources. This community service activity aims to optimize the digital literacy of elementary school teachers and students by establishing a teacher learning community as a platform for ongoing mentoring. The activity was implemented through five stages: needs mapping, learning community formation, gradual training, collaborative practice between teachers, and reflective evaluation. The target group included classroom teachers and students at a partner elementary school. The results of the activity demonstrated an increase in teachers' digital competency, not only individual but also through the process of sharing good practices among teachers in community forums. Students also demonstrated improved digital literacy skills, particularly in recognizing trustworthy information. In conclusion, the mentoring model based on a teacher learning community has proven to be an effective and sustainable strategy for optimizing digital literacy to improve the quality of learning in elementary schools.